KERAGAAN GENETIK IKAN SIDAT (Anguilla marmorata) DARI PERAIRAN POSO BERDASARKAN POLIMORFISME MITOKONDRIA DNA D-LOOP [Genetic Appearances of Eel (Anguilla marmorata) from Poso Waters Based on Mitochondria Polymorphism DNA D-loop] - Triyanto Triyanto; Lukman Lukman; Djamhuriyah S. Said (Jurnal Iktiologi Indonesia, 2008)
Anguilla marmorata is the dominant eel found in Poso. It has the largest body size and distributes on all habitat types especially the lake and the river of Poso. As catadromous fish, the larvae of eel grow in marine ecosystem which subsequently migrates and develops in freshwater ecosystem such as lakes and rivers. Information concerning variance of morphologies from the eel has been known but biological information especially in genetic not yet many reported. A. marmorata from various locations in Lake Poso (Pendolo, Tentena, Solokaya) and River Poso (Pandiri and estuary) was examined using polymorphism of the mitochondria DNA (mtDNA) D-loop markers. Four composite haplotypes were detected using digestion of D-loop sequences with five endonucleases: HaeIII, Hin61, /?sal, Taq\, and NdeII. There was no significant difference observed on the genetic variation among the eel populations.